1999
DOI: 10.1590/s0103-84781999000200021
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência de alevinos de Jundiá (Rhamdia quelen Quoy & Gaimard, 1824) à variação de salinidade da água

Abstract: correspondência. de 8,0; 9,0; 9,25; 9,50 e 10,0g/l de sal marinho comum ou 10,0; 12,0 8.0, 9.0, 9.25, 9.5, or 10.0g/l common marine salt or 10.0, 12.0, or 14.0‰ artificial seawater. Survival was observed over a period of 96h. The control group was maintained in the same conditions, but with salinity of 0‰. There was no mortality and change of behavior in the groups exposed to 8g/l common marine salt and to 10‰ seawater. The group exposed to 9g/l common marine salt also did not show mortality, but there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
2
7
0
8
Order By: Relevance
“…O jundiá (Rhamdia quelen) é uma espécie de peixe reofílica pertencente à ordem Siluriformes (Nakatani et al, 2001) encontrado nas Américas Central e do Sul (Silfvergrip, 1996;Baldisserotto, 2004). É uma espécie nativa capaz de tolerar baixas temperaturas, apresentando bom crescimento no inverno e verão, principalmente, no sul do Brasil (Piaia & Baldisserotto, 2000), alto rendimento de carcaça, carne de ótimo sabor (Barcelos et al, 2003) e boa aceitação no mercado consumidor (Marchioro & Baldisserotto, 1999).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O jundiá (Rhamdia quelen) é uma espécie de peixe reofílica pertencente à ordem Siluriformes (Nakatani et al, 2001) encontrado nas Américas Central e do Sul (Silfvergrip, 1996;Baldisserotto, 2004). É uma espécie nativa capaz de tolerar baixas temperaturas, apresentando bom crescimento no inverno e verão, principalmente, no sul do Brasil (Piaia & Baldisserotto, 2000), alto rendimento de carcaça, carne de ótimo sabor (Barcelos et al, 2003) e boa aceitação no mercado consumidor (Marchioro & Baldisserotto, 1999).…”
Section: Introductionunclassified
“…É uma espécie nativa capaz de tolerar baixas temperaturas, apresentando bom crescimento no inverno e verão, principalmente, no sul do Brasil (Piaia & Baldisserotto, 2000), alto rendimento de carcaça, carne de ótimo sabor (Barcelos et al, 2003) e boa aceitação no mercado consumidor (Marchioro & Baldisserotto, 1999).…”
Section: Introductionunclassified
“…Kubitza (2007) recommends that common salt (NaCl) in concentrations between 10 and 50 g/L can be used to control protozoan parasites and Monogenea (exposure time between 12 hours and 20 seconds), whereas Souza-Bastos and Freire (2009) suggest 15 g/L concentration of exposure time of one hour for the treatment of Ichthyophthirius multifiliis Fouquet, 1876 in silver catfish (R. quelen). Marchioro and Baldisserotto (1999) concluded that R. quelen accepted NaCl concentrations in water up to 9 g/L for 96 hours without any death, albeit with changes in feed behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Selosse & Rowland (1990) também observaram o efeito positivo do sal comum (5 g L -1 ) no controle do ictio em várias espécies de peixes tropicais. Marchioro (1997) afirmou que o jundiá pode suportar altas concentrações de sal comum por longo período (9,0 g L -1 por 96 horas), permitindo seu uso em banhos terapêuticos sem maiores problemas. Como vantagens para este tratamento encontram-se a facilidade de aquisição do produto e a ausência de restrições de uso em peixes destinados ao consumo humano (Pavanelli et al, 1998).…”
Section: Ichthyophtirius Multifiliis In Rhamdia Quelenunclassified